Wavelet maxima mapping quantiser for image lowpass approximation subband coding - Teow, M.; Lee, Sze-Wei; Chai, I. (2003)
A new wavelet oriented scalar quantisation method called wavelet maxima mapping quantisation that uses the spatially adaptive wavelet maxima map to determine the quantisation index for lowpass approximation subband magnitude is proposed. Empirical analysis shows that substantial peak signal-to-noise ratio gain can be obtained at relatively low bit rate cost.